Community perception, community satisfaction, and social interaction in the Metropolitan fringe patterns in the Oak Ridges Moraine North of Toronto - Beesley, Kenneth B. (Truro , Nova Scotia, Canada Department of Humanities, Nova Scotia Agricultural College and Rural Research Centre, 1995)
The social nature of metropolitan fringe environments is linked to a series of interrelationships, principally between people and between people and the land. InSouthern Ontario a major land use is agriculture, with this industry firmly entrenched in the landscape, even in the expanding urban region around Metropolitan Toronto. Equally important, and in contrast to agricultural activity, is nonfarm development, which contributes substantially and increasingly to social patterns in the city's countryside. Within this mixed environment, people reside in communities they perceive differently, articulate varying levels of satisfaction with, and within which they experience diverse social interactions. This paper represents an attempt to focus on three themes : community perception, community satisfaction, and social interaction, all within the context of a portion of the metropolitan fringe north of Toronto.
Rural Studies Working Papers No. 11
Keywords: Metropolitan fringe environments